Epidemiological Profile, Anthropometric Indicators, and Risk Factors of Anterior Cruciate Ligament (ACL) Injuries Among Male Athletes: An Extensible Descriptive-Exploratory Study in Chlef Wilaya - Lahouari, Ziane; Taieb, Gueracha; Mohamed, Ouddak; Abderezzek, Boudouani (Journal of Ecohumanism, 2026)
Background: Anterior Cruciate Ligament (ACL) injuries present a critical structural and functional threat to athletes, often necessitating surgical intervention and inducing long-term joint instability. Objective: This extensible study investigated the epidemiological characteristics, anthropometric indicators, workload variables, and environmental factors associated with ACL tears among male athletes in Chlef Wilaya. Methodology: A descriptive-exploratory cross-sectional design was applied to a baseline sample of N = 36 male injured athletes. Precise physical parameters and injury environmental dynamics were processed using JAMOVI (v2.4). Both descriptive metrics and inductive statistics via Pearson’s Chi-Square (χ²) were deployed. Results: The cohort exhibited a mean BMI of 24.16 ± 2.98 kg/m2. Team sports—specifically Handball (55.6%) and Soccer (36.1%)—predominated the sample. Critically, 63.9% of ACL tears occurred on high-friction Multi-sports halls and 25.0% on Artificial grass during active exercise (97.2%). Inductive analysis revealed a statistically significant association between the flooring type where the tear occurred and the sport discipline (χ² = 38.6, p < 0.001). Conclusion: ACL failure in Chlef is highly multifactorial, driven by elevated mechanical loading and interaction with high-torque synthetic and turf fields. This registry remains open for prospective database expansions.